Fulfillment of News Functions and Values on News Photo in Local newspapers - Jumiati, Rahma Yani; Syas, Mulyanti (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2018)
One interesting part of the newspaper is the presence of visualization in the form of pictures or photos called news photos. There are six functions of news photos, namely; as a complement to the news text in a news, reinforcement and news quality provider, giving interest to readers' interest, information function, educating function and human interest. Besides having to fulfill its function, a news photo that will be presented must also contain news value. There are six categories of news values, namely; novelty, closeness, important people, conflict, information and consequences. This article will discuss the fulfillment of the function and news value of a news photograph in the Singgalang newspaper, which is the  local newspaper in West Sumatra, whose ideal has been to notice its function and value of its photojournalism. This study was carried out with quantitative approaches with descriptive "content analysis" techniques.  This study found that the Singgalang newspaper fulfilled the function of news photos as much fifty-three percent (53%), and the value of news photos that could be fulfilled in Singgalang newspaper was sixty one percent (61%). The conclusion that can be drawn from this study is that Singgalang newspaper still lacks the importance of the function and value of the news on the photo news presented.